2015
DOI: 10.1016/j.regsciurbeco.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration and job matching among college graduates

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 36 publications
1
26
0
4
Order By: Relevance
“…Many take jobs that use their education very little, and some take jobs for which they are overeducated (Robst 2007a,b;Abel and Deitz 2012b). Furthermore, part of the value of a college education is that it is a credential that signals one's innate ability to employers, independent of the knowledge and skills gained.…”
Section: Background On Human Capital Externalities the Creative Clasmentioning
confidence: 99%
“…Many take jobs that use their education very little, and some take jobs for which they are overeducated (Robst 2007a,b;Abel and Deitz 2012b). Furthermore, part of the value of a college education is that it is a credential that signals one's innate ability to employers, independent of the knowledge and skills gained.…”
Section: Background On Human Capital Externalities the Creative Clasmentioning
confidence: 99%
“…Duranton and Puga [7] presented a theoretical foundation that shows that improving the quality and frequency of matching employees with firms serves as a channel through which local labor pooling contributes to the productivity of local firms. Abel and Deitz [8] provided empirical findings that a thick labor market helps college graduates in the United States find jobs that more closely match their education. Andini et al [13] examined four aspects of local labor pools, including turnover, learning, matching, and hold up, and their Italian empirical analysis showed a positive association between turnover and on-the-job training and labor market density.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urban economic theorists have developed models related to the concentration of various firms and production factors in a city and their generation of urban advantages: sharing specialized production inputs, enhancing learning and spreading specific knowledge, and facilitating higher-quality matches between workers and firms [7]. In particular, a thick labor market represents a source of agglomeration economies by reducing employee search costs, increasing churning rates, and improving the likelihood of strong matches between workers and firms [8,9]. This line of study has indicated that a large local labor pool has a positive effect on both firms and workers during job searches and matching processes in populated urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Например, оценки вероятно-стей согласования знаний выпускников и требований вакансий (Abel, Deitz, 2015;Gan, Li, 2016) показали, что области специализации, где больше ва-кансий и больше кандидатов, демонстрируют более высокие показатели со-гласования полученного образования и требований нанимателей. Другим примером является работа Д. Коста и М. Кан (Costa, Kahn, 2000), где рассма-тривается выбор места жительства супругов, оба из которых имеют высшее образование и степень колледжа.…”
Section: источники и механизмы агломерационной экономики городаunclassified